EVALUASI PROKSEMIK PUSAT LAYANAN KESEHATAN YANG MENERAPKAN PROTOKOL KESEHATAN (STUDI KASUS: PUSKESMAS INDUK KEDUNG BADAK BOGOR) - Rizka Alya Triztika; Sangayu Ketut Laksemi; Achmad Syarief (Universitas Trisakti, 2021)
Abstract : Corona virus (Covid-19) is becoming a pandemic in the world, in Indonesia there are several red zones which are categorized as the most spread of the virus, one of which is the city of Bogor, one of the most vulnerable places is health service centers such as hospitals, clinics and also a community health center. The public health center in Bogor City has maximized efforts to reduce the spread of the virus by paying attention and improving health protocols. Based on these issues and phenomena, this study will examine the proxemics compromise distance in the Community Health Center room, with study case Kedung Badak Community Health Center. The study aims to identify the compromise distance that occurred in Kedung Badak Community Health Center, Bogor City during the pandemic as well as to identify visitors' understanding of health protocols regarding social distancing in public service spaces using questionnaire data, which aims to confirm social distance information, activities and facilities. given by Kedung Badak Community Health Center, understanding of visitors, patients and health workers related to social distancing which is regulated based on protocols, using descriptive quantitative research methods, the procedure used in this study is questionnaire, to solve problems regarding patient and visitor understanding about social distance, as well as an evaluation of observations to identify any compromises that occurred in Kedung Badak Community Health Center. From the identification results, it was found that there were differences in the perceptions of health workers and visitors regarding information on health protocols to maintain distance, there was a compromise distance starting with intimate distance to personal distance due to limited space and existing facilities. The focus of study is directed at the visitor's understanding as well as the progression bubble which results in compromising distances.Keywords: Covid19, Health Protocol, Proxemics, Compromise Distance.Abstrak : Corona virus (Covid-19) menjadi sebuah pandemi di dunia kesehatan, di Indonesia sendiri terdapat beberapa zona merah yang dikategorikan sebagai penyebaran virus terbanyak, salah satunya adalah Kota Bogor, salah satu tempat yang paling rawan adalah pusat layanan kesehatan seperti rumah sakit, klinik dan juga pusat kesehatan masyarakat. Pusat kesehatan masyarakat (PKM) di Kota Bogor telah memaksimalkan upaya agar mengurangi penyebaran virus dengan memerhatikan dan meningkatkan protokol kesehatan, Berdasarkan isu dan fenomena tersebut, penelitian ini akan mengkaji jarak kompromistis proksemik pada ruang Pusat Kesehatan Masyarakat, dengan studi kasus Puskesmas Kedung Badak di kota Bogor. Penelitian bertujuan untuk mengidentifikasi jarak kompromi yang terjadi pada PKM Kedung Badak Kota Bogor pada masa pandemi, serta mengidentifikasi pemahaman pengunjung tentang protokol kesehatan mengenai menjaga jarak sosial pada ruang layanan publik menggunakan data kuesioner, yang bertujuan untuk mengkonfirmasi informasi social distance, aktifitas dan juga fasilitas yang diberikan oleh PKM Kedung Badak, pemahaman pengunjung, pasien dan petugas kesehatan terkait dengan social distancing yang diatur berdasarkan protokol, dengan menggunakan metode penelitian deskriptif kuantitatif, prosedur yang digunakan dalam penelitian ini berupa kuesioner, untuk memecahkan masalah mengenai pemahaman pasien dan pengunjung mengenai menjaga jarak, serta adanya evaluasi observasi untuk mengidentifikasi adanya jarak kompromi yang terjadi di PKM Kedung Badak. Dari hasil identifikasi maka ditemukan perbedaan persepsi petugas kesehatan dengan pengunjung mengenai informasi protokol kesehatan menjaga jarak, timbul nya jarak kompromi dimulai dengan jarak intim hingga jarak personal yang dikarenakan keterbatasan ruang dan fasilitas yang ada. Fokus kajian diarahkan pada pemahaman pengunjung serta gelembung prokmesik yang mengakibatkan adanya jarak kompromistis.Kata Kunci : Covid19, Protokol Kesehatan, Proksemik, Jarak Kompromi.